Versatile Humanoid Robots for Theatrical Performances. (4th January 2013) - Lin, Chyi-Yeu; Cheng, Li-Chieh; Huang, Chun-Chia; Chuang, Li-Wen; Teng, Wei-Chung; Kuo, Chung-Hsien; Gu, Hung-Yan; Chung, Kuo-Liang; Fahn, Chin-Shyurng
The purpose of this research is to develop multi-talented humanoid robots, based on technologies featuring high-computing and control abilities, to perform onstage. It has been a worldwide trend in the last decade to apply robot technologies in theatrical performance. The more robot performers resemble human beings, the easier it becomes for the emotions of audiences to be bonded with robotic performances. Although all kinds of robots can be theatrical performers based on programs, humanoid robots are more advantageous for playing a wider range of characters because of their resemblance to human beings. Thus, developing theatrical humanoid robots is becoming very important in the field of the robot theatre. However, theatrical humanoid robots need to possess the same versatile abilities as their human counterparts, instead of merely posing or performing motion demonstrations onstage, otherwise audiences will easily become bored. The four theatrical robots developed for this research have successfully performed in a public performance and participated in five programs. All of them were approved by most audiences.